The Influence of Digital Marketing and Perceived Ease of Use on Consumer Purchase Intention in the Shopee Marketplace - armansyah Msarusu; Jajang Suherman; Mutiara Ramadhani Latif Latif (Masoem University, 2026)
The rapid development of digital technology has significantly influenced consumer shopping behavior, particularly through online marketplaces. This study aims to analyze the influence of digital marketing and perceived ease of use of the Shopee marketplace on consumer purchase intention. The research was conducted among Shopee users in Indonesia who had previously made transactions on the platform. A quantitative research design with a survey approach was employed, involving 110 respondents selected using purposive sampling. Data were collected through structured questionnaires and analyzed using multiple linear regression. The results show that digital marketing has a positive and significant effect on consumer purchase intention (? = 0.421; p < 0.05). Perceived ease of use also has a positive and significant effect on purchase intention (? = 0.356; p < 0.05). Furthermore, the simultaneous test indicates that digital marketing and perceived ease of use significantly influence consumer purchase intention (F = 42.317; p < 0.05). These findings highlight the importance of effective digital marketing strategies and user-friendly platform design in increasing consumers’ intention to purchase through online marketplaces.